Interspecific mating: Is the frequency of the potential partners relevant? - Cabaña, Imanol; Gardenal, Cristina Noemí; Chiaraviglio, Margarita; Rivera, Paula Cecilia (2022)
FIL: Cabaña, Imanol. Universidad Nacional de Córdoba. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Diversidad y Ecología Animal; Argentina.